Fulfillment of Detainees' Rights at the Detention Center Based on National Police Chief Regulation No. 4/2015 on Detainee Care at Polda Bali - I Komang Mulyacandra; Ni Ketut Wiratny; I Nyoman Suandika (PT Publikasiku Academic Solution, 2025)
Regulation of the Chief of Police of the Republic of Indonesia Number 4 of 2015 concerning the treatment of detainees is the basis for the implementation of the duties of police officers of the Bali Police Detention and Evidence Directorate. This study aims to identify and analyze the fulfillment of detainees' rights at the Bali Police Detention Center, as well as to find out the factors that become obstacles in the implementation of the protection of these rights. This type of research uses a normative legal approach supported by empirical with data collection techniques through literature studies, interviews, and observations. The analysis is carried out descriptively and prescriptively to provide a clear picture of the conditions for the fulfillment of detainees' rights. The results showed that the implementation of the fulfillment of detainees' rights in accordance with National Police Chief Regulation Number 4 of 2015 still faces various obstacles. Bali Police detention centers can only implement the provisions stipulated in Article 10, while the provisions in Article 7 governing the placement of detainees are still not optimally implemented. The main obstacle in the implementation of the fulfillment of detainees' rights is caused by the large number of detainees held and limited facilities. Improvement efforts that have been made include the application for the construction of a new building and the loan of special placement cell space. In conclusion, to improve the fulfillment of detainees' rights at the Bali Police Detention Center, there needs to be more attention from the police and adequate policy support, so that all provisions in the National Police Chief Regulation can be implemented optimally and the rights of detainees can be fulfilled properly.